The role of chemoradiation therapy in locally advanced pancreatic cancer - White, Rebekah R. (2005)
The majority of patients with pancreatic cancer present with disease that is unresectable due to local invasion. This article reviews the evidence (or lack thereof) that chemoradiation therapy (CRT) helps these patients in four areas: survival, tumor downstaging, palliation of obstructive symptoms, and pain control. We believe that CRT allows a small percentage of patients with locally advanced disease to undergo potentially curative resection while providing effective palliative treatment.